Managerial antecedent factors of export market-oriented organizations and their performance consequences: Studying hungarian higher education institutions using a configurational approach - Berács, József; Nagy, Gábor (Vezetéstudomány / Budapest Management Review, 2022)
The study focuses on the managerial antecedents of export market-orientation and tests the complex interaction of these factors to two outcomes of interest (that is, high export market performance vs. the absence of high export market performance) with a fuzzy-set qualitative comparative analytical approach (fsQCA). Using a combined survey data of twenty five export-orientated higher education institutions based in Hungary the results show that a complex interaction of ma- nagerial antecedents factors to export market-orientation and export market-orientation leads to a high export market performance, whereas misfit between these factors yields the absence of a high export market performance; a complex analytical and theoretical approach missing from export market-orientation and strategic human resource management literatures. Results of the study can enrich the understanding of the complex interaction of the managerial antecedent factors to export market-orientation; therefore, providing valuable insights to academic and managerial audiences ali